Religious thoughts of Sir Sayyid Ahmad Khan (1817-1898): an analytical study - Gilani, Sayyid Muhammad Yunus; Al-Masud, Abdullah (2016)
Sir Sayyid Ahmad Khan (1817-1898) was a dynamic force against conservatism,